2022
DOI: 10.1186/s12933-022-01623-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of fibrin amyloid microclots in long COVID/post-acute sequelae of COVID-19 (PASC) shows many entrapped pro-inflammatory molecules that may also contribute to a failed fibrinolytic system

Abstract: Background Post-acute sequelae of COVID-19 (PASC), also now known as long COVID, has become a major global health and economic burden. Previously, we provided evidence that there is a significant insoluble fibrin amyloid microclot load in the circulation of individuals with long COVID, and that these microclots entrap a substantial number of inflammatory molecules, including those that might prevent clot breakdown. Scientifically, the most challenging aspect of this debilitating condition is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(166 citation statements)
references
References 110 publications
3
162
0
1
Order By: Relevance
“…We have found that α-2AP is trapped inside microclots (10,19). This molecule prevents the fibrinolytic system from functioning optimally and impedes the digestion of pathological thrombi that cause microvascular thrombosis, thereby increasing the risk of thromboembolic events (10,19).…”
Section: α-2-antiplasminmentioning
confidence: 99%
See 4 more Smart Citations
“…We have found that α-2AP is trapped inside microclots (10,19). This molecule prevents the fibrinolytic system from functioning optimally and impedes the digestion of pathological thrombi that cause microvascular thrombosis, thereby increasing the risk of thromboembolic events (10,19).…”
Section: α-2-antiplasminmentioning
confidence: 99%
“…Participant identification for ELISA analysis For the enzyme-linked immunosorbent assay (ELISA) analysis, we randomly selected a subset of stored Long COVID and healthy samples, where we previously confirmed entrapped inflammatory molecules using proteomics analysis (10) (see Table 1). The sample included blood collected from 15 healthy individuals to serve as controls (1 male; 14 females; median age 42 ) and 25 Long COVID patients (9 males; 16 females; median age 52 ).…”
Section: Patient Demographicsmentioning
confidence: 99%
See 3 more Smart Citations